Toolkit for strategic assessment of the level of environmental safety of construction enterprises in a digital and risk-oriented context - Malykhina, O.; Fedun, I.; Nikolayko, D.; Movsesyan, A.; Lytarev, A. (Ways to Improve Construction Efficiency, 2024)
This paper examines the toolkit for the strategic assessment of the level of environmental safety of construction enterprises in a digital and risk-oriented context. It emphasizes that under current global transformations, the environmental aspects of the construction industry are becoming no less important than economic or technological ones. Modern enterprises are forced to adapt to the strengthening of environmental requirements, increasing social pressure, and the necessity of minimizing risks that arise in the production process. The use of digital technologies, such as environmental impact monitoring systems, risk management platforms, and analytical tools, makes it possible to create more accurate and comprehensive models for assessing environmental safety. Special attention is paid to the analysis of risk-oriented approaches, which allow integrating the results of strategic assessment into managerial decision-making. This ensures the ability to forecast probable scenarios of the environmental impact of construction enterprises and to develop strategies for preventing and minimizing ecological threats. An important component is the assessment of the enterprise’s resource base, which includes technological, financial, and human resources that form the potential for improving the level of environmental safety. The study also highlights the role of BIM technologies, artificial intelligence systems, and big data in forming transparent and adaptive mechanisms of environmental control. This makes it possible to increase the accuracy of environmental forecasts, the speed of information processing, and the efficiency of managerial decisions. The concept of integrating digital management platforms with environmental management systems is considered as a means of ensuring the sustainability of enterprises in the long-term perspective. The obtained results lead to the conclusion that strategic assessment of the level of environmental safety is an essential component of the modern management model of a construction enterprise. The use of digital technologies and risk-oriented methods enables the formation of a systematic approach that ensures a balance between economic efficiency and environmental responsibility. The proposed toolkit can be used as a theoretical basis for further research and practical developments, as well as a methodological guideline for managers seeking to ensure competitiveness in today’s dynamic market environment.